مراحل تنزيل الحكم الشرعي وضوابطه في ضوء منهج الوسطية - Al-Quradghi, Arif Ali Arif; Ahmad, Kosrat Salih (Centre for Muslim World Affairs International Islamic University Malaysia, 2016)
This research aims at investigating the necessary stages and ruling controls required in the process of identification of Sharia rulings to attain the principle of moderation so that it runs its course correctly and soundly without deviation or equivocation. The research problem indicates to those stages and controls that have real effect on the extraction of the grounds of the rulings and which implementation is necessary for the community and individuals, whilst mentioning the requirements and limitation of the application of these standards. The researcher endeavors to answer the following questions: What is the concept of Sharia ruling identification? What are these necessary stages and controls required in the process of rulings’ identification? To answer these questions, the iintrospective approach and analysis have been adopted to achieve the objectives. The research journey concluded that these stages include “perception, adaptation, and the implementation” if the Islamic scholar unable to reach the specific Islamic ruling, he has to stop. Besides that, he has to taking into accounted the necessary ruling controls, which most important: “easing and lifting of embarrassment, and taking into account the jurisprudence of priorities, and freedom from intolerance and blind imitation, and taking into account the values, explanation and clarification”. These stages and ruling controls should be considered to achieve the moderation path in adopting the Sharia ruling both in Individual or collective ijtihad; as any approach without these stages and ruling controls whereby they are not utilized fully is not a moderate approach but an illusion. The study consists of two main axes: an explanation of the research terms, such as the statement of the concept of moderation and the application of the Sharia ruling. The second axis contains those stages and controls that must be available in the rulings’ identification approach to be a moderate and neutral between the parties, void of excess or negligence.